The Influence of Biological Feed Additives on Broiler Performance - El-Husseiny, O.M.; Abdallah, A.G.; Abdel-Latif, K.O. (International Journal of Poultry Science, 2008)
An experiment was designed to evaluate the effect of some natural feed additives as alternatives of antibiotic growth promoters for broiler chicks. A total number of 1188 unsexed one-day old Ross 308 chicks were used. Two trials were conducted simultaneously using the same control treatments, a negative control (NC) with no feed additive and a positive control (PC) supplemented with Enramycine (0.025%) as antibiotic growth promoter. In the fist trial, natural mineral clay commercial products of Diatomaceous earth1, at 0.2% (DE0. 2%) and 0.5% (DE0. 5%) and Farmagulator2, at 0.125% (Fg. 125%) and, 0.25% (Fg 0.25%) were compared with the control treatments. In the 2nd trial, pre/pro-biotics commercial products of Diamond VXPC3, 0.075% (DV 0.075%) and 0.10% (DV 0.10%); Tomoko4, 0.05% (Tom 0.05%) and 0.1% (Tom 0.1%); and Primalac5, 0.15% (PL 0.15) were compared with the two control treatments. Diets were formulated to meet nutrient requirements of chicks recommended for Ross 308. Results indicated that performance and immune response of the chicks fed diets containing pro/pre-biotic products were higher than those fed diets containing natural mineral clay products. The positive control or the treated group significantly recorded higher body weight than the negative control, with an exception of Diatomaceous earth treatment. Diatomaceous earth treatments (0.2% or 0.5%) significantly recorded the worst performance and the lowest economical efficiency compared to the negative control or the other treatments. From commercial point of view, biological feed additives of pre/pro-biotics or natural mineral clay as alternative of antibiotic growth promoter are beneficial with exception of Diatomaceous earth. Diets supplemented with biological feed additives enhanced the digestibility coefficients of most nutrients better than the controls, however, DE lowered the digestibility coefficients of most nutrients. It is concluded that performance and immune response of chicks fed on biological feed additives were equivalent or even superior to that of antibiotic growth promoter except for Diatomaceous earth. The tested materials were superior to the negative control when added to the diet in the term of performance.